A CONTRIBUTION OF STUDENTS’ MOTIVATION AND THEIR SPEAKING ABILITY AT SECOND GRADE OF SMA NEGERI 1 TEMBILAHAN HULU - Friskila Eka Pratiwi; Agus Mustajib; Maizarah (J-Shelves of Indragiri (JSI), 2023)
This research aimed to determine the correlation between students' motivation and speaking ability in the second-grade class of MIPA 1 at SMAN 1 Tembilahan Hulu. The researcher identified several problems based on the background of the problem, namely, a lack of motivation to speak English and some students suggesting the teacher use Indonesian. Students are rarely motivated to practice speaking, and some are afraid to use English. The design of this research is correlational research. The population in this study was 134 students in the second grade of MIPA at SMAN 1 Tembilahan Hulu, which consisted of 5 classes. The researcher chose one class, namely class XI MIPA 1, from the population sample of 34 students in this research. This study examines the relationship between students' motivation and their speaking ability. To obtain research data, the researcher gave a questionnaire consisting of 10 question items and a speaking test to 34 samples with raters 1 and 2, namely the English teacher and the researcher. The findings of this study indicate that the motivation from the questionnaire, the total score of Students' Motivation on Speaking English, and their Speaking Ability are 73%, or between the range of 59% and 88% in the average category. In class XI, MIPA 1 was the average motivation. The result of their speaking ability is 26.4% in the Very High category, 32.3% in the High category, 29.4% in the Medium category, and 11.7% in the Low category. The analysis results show that the Alternative Hypothesis (Ha) is rejected if r is observed at the significance level, which means no correlation exists between students' motivation and speaking ability. The Null Hypothesis (Ho) is accepted if r is observed at the significance level, which means a correlation exists between students' motivation and speaking ability. The researcher got r calculated at -0,063, which is lower than the significance level. It means that Ho is accepted and Ha is rejected. This means no significant correlation exists between students' motivation and their speaking ability at XI MIPA 1 of SMAN 1 Tembilahan Hulu.